2020
DOI: 10.1111/jac.12435
|View full text |Cite
|
Sign up to set email alerts
|

“Macaíba, an emerging oil crop: Nutritional evaluation of the pulp and kernel fruits from semi‐arid and coastal zone of northeast Brazil

Abstract: Many native species of the Brazilian flora are still little explored economically in the country. An example is Acrocomia intumescens, a palm tree that in recent studies has shown some industrial potential still unexplored. The present study evaluates the proximate composition, including minerals, and total carotenoid content of A. intumescens fruits from three different locations in Pernambuco State, north‐east Brazil, with distinct climatic characteristics. A. intumescens fruits showed that nutritional compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…The genus Acrocomia can be found in a wide geographic distribution due to its adaptation to different climates [1]. Acrocomia aculeata (Jacq.)…”
Section: Botanical Taxonomy (Acrocomia Aculeata)mentioning
confidence: 99%
See 3 more Smart Citations
“…The genus Acrocomia can be found in a wide geographic distribution due to its adaptation to different climates [1]. Acrocomia aculeata (Jacq.)…”
Section: Botanical Taxonomy (Acrocomia Aculeata)mentioning
confidence: 99%
“…Acrocomia aculeata, also known as macaúba or bocaiuva, is a common and economically important palm species in Brazil, especially in the state of Mato Grosso do Sul. Several studies have explored its nutritional properties, both of the pulp and kernels, as shown in Table 1, revealing its potential as a source of nutrients and vegetable oils [1]. However, this fruit is still exploited in an extractive manner, and the process of removing the skin is on a small scale [16].…”
Section: Nutritional Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few studies assessing the potential and quality of macaíba pulp and oil [22,24]. A research confirmed the anti-inflammatory and diuretic activities of the pulp's oil in rats [25].…”
Section: Introductionmentioning
confidence: 99%